Transformative Educational Leadership of Ahmad Dahlan and its Relevance to the Development of Muhammadiyah Education - Syahrul Syahrul (SHS Web of Conferences)
The success of an educational institution is largely determined by its leaders. Leadership is a very crucial aspect, perhaps even the most important in an organization. To face the very complex challenges of future education, transformative educational leaders are needed. Muhammadiyah has crossed the ages with the development of its charitable educational endeavors. All of this cannot be separated from the transformative educational leadership of Ahmad Dahlan, the Muhamadiyah founder. This research will explore the characteristics of transformative leadership and its relevance to the development of Muhammadiyah education. By using the literature research method (library research) it was found that Ahmad Dahlan has all the characteristics of a transformative educational leader. Such as a) Having charisma; b) Always present intellectual stimulation; c) Having attention and concern for each individual follower; d) Motivation that inspires followers; e) Trying to increase the capacity of its followers; f) Give more examples than talk a lot. The relevance is in the inheritance of the three main values of Ahmad Dahlan’s leadership: sincerity and exemplary; continuous progress and innovation; and lifelong education in Muhammadiyah educational institutions ranging from primary, secondary and tertiary levels.